2021
DOI: 10.1051/metal/2021016
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review: The electromagnetic field arrangement and the “braking” effect of electromagnetic brake (EMBr) technique in slab continuous casting

Abstract: Electromagnetic brake (EMBr) technique is adopted to reduce the turbulence of molten alloy in the slab mould in the continuous casting process, especially under high casting speed. We introduce a state-of-the-art EMBr technique by reviewing the published literature. The main objective of this paper is to give a clear view of the EMBr technique in terms of the magnet arrangement, along with their “Braking” effect to help decision-making. The EMBr system can be divided into three types, in terms of the magnet ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Li et al discussed the braking effect per magnetic field arrangement and showed the advantages and disadvantages for each type of EMBr unit. For the local type EMBr, it can be further divided into four main types: the first generation local type EMBr, upper jet-pattern EMBr, jet-pattern EMBr, and local vertical EMBr [ 7 ]. The first generation local type EMBr was used and simulated in our research.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al discussed the braking effect per magnetic field arrangement and showed the advantages and disadvantages for each type of EMBr unit. For the local type EMBr, it can be further divided into four main types: the first generation local type EMBr, upper jet-pattern EMBr, jet-pattern EMBr, and local vertical EMBr [ 7 ]. The first generation local type EMBr was used and simulated in our research.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the transient flow inside the mold, electromagnetic brake (EMBr) appliance has been applied in slab continuous caster, especially at the high casting speed. [10][11][12] Up to now, EMBr has traditionally been classified into three typical types: local, single-ruler, and double-ruler (knows as FC-Mold). [13] Generally, EMBr is used to stabilize the fluctuation of the steel/slag interface [14,15] and alleviate the remelting of solidified shell at mold narrow face, [16,17] while this technique has recently been shown to improve asymmetric flow caused by slide-gate or SEN clogging.…”
Section: Introductionmentioning
confidence: 99%
“…The EMBr technology can solve the problem of turbulent flow of molten steel caused by a high casting speed. According to the different arrangement of the applied magnetic field, the forms of electromagnetic brake mainly include Local EMBr, EMBr ruler, FC mold, Vertical electromagnetic brake, and some new forms of electromagnetic brakes [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Processes 2021, 9, x FOR PEER REVIEW 2 of 13 magnetic brake mainly include Local EMBr, EMBr ruler, FC mold, Vertical electromagnetic brake, and some new forms of electromagnetic brakes [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%